Techniques of providing data integrity in cloud computing - David Raju, K; Vijay Kumar, K; Rahul Showry, K Anthony; Lohit Krishn, B (International Journal of Engineering and Technology, 2017)
The Data Integrity is simply termed as no corruption in the data that can be assured with consistency and accuracy over the time Precisely it can be defined as the data should be recorded as the Original and at the time of retrieval it should ensure that it send the Original recorded data. Data Integrity is the fundamental component of Information Security. Every technique of data integrity ensures the no loss in flow of data. We start with briefing about Data Integrity and Cloud Computing and then briefing Data Integrity models. After this, we examine General strategies that guarantee information uprightness, Challenges in Cloud Computing, Techniques in cloud to guarantee information honesty to be specific provable information ownership and verification of retrievability and their disadvantages and their confinements over some particular cases. This paper is Standardized investigation of existing system for the guaranteeing the information trustworthiness in cloud and another strategy is proposed. This paper is Standardized analysis of existing mechanism for the ensuring the data integrity in cloud and a new method is proposed.